The Implementation of Learning Policies in the New Normal Era in Garut Regency - Rostiena Pasciana; Friska Prastya Harlis; Ieke Sartika Iriany; Sri Farida (Universitas Jambi, Indonesia, 2022)
The unpreparedness of the community in rural areas with government policies related to change in learning methods during the pandemic is a rife phenomenon in Indonesia's education sector. As is the case in one public junior high school, Garut Regency, there were limited resources, weak control over the learning process, and a lack of support from parents. This research aims to describe the implementation of learning policies in one public junior high school, Garut Regency in the new normal era and its impacts. This study uses qualitative methods with descriptive analysis. Informants in this study were principals, teachers, and students. By analyzing communication, resources, disposition, and bureaucracy structure, the result shows that the implementation of blended learning has not been optimal. Implementing blended learning requires good cooperation between the school, students, and the community. In addition, providing technology-based education training to teachers and staff, increasing students' digital literacy, and increasing parental socialization are very important things to strive for.